Bacteriology and clinical outcomes of patients with culture‐positive pleural infection in Western Australia: A 6‐year analysis. Issue 2 (6th September 2018) - Brims, Fraser; Popowicz, Natalia; Rosenstengel, Andrew; Hart, Julie; Yogendran, Arthee; Read, Catherine A.; Lee, Felicity; Shrestha, Ranjan; Franke, Alexander; Lewis, Joshua R.; Kay, Ian; Waterer, Grant; et al.
ABSTRACT: Background and objective: Pleural infection is a clinical challenge; its microbiology can be complex. Epidemiological and outcome data of pleural infection in adult Australians are lacking. We describe the bacteriology and clinical outcomes of Australian adults with culture‐positive pleural infection (CPPI) over a 6‐year period. Methods: Cases with CPPI were identified through Western Australian public hospitals electronic record. Culture isolates, admission dates, vital status, co‐morbidities, radiology, blood and pleural fluid tests were extracted. Results: In total, 601 cases (71.4% males; median age: 63 years (IQR: 50–74); median hospital stay 13 days) involving 894 bacterial isolates were identified. Hospital‐acquired (HA)‐CPPI was defined in 398 (66.2%) cases, community‐acquired (CA)‐CPPI in 164 (27.3%) cases and the remaining classified as oesophageal rupture/leak. Co‐morbidities, most frequently cancer, were common (65.2%). Radiological evidence of pneumonia was present in only 43.8% of CA‐CPPI and 27.3% of HA‐CPPI. Of the 153 different bacterial strains cultured, Streptococcus species (32.9%) especially viridans streptococci group were most common in CA‐CPPI, whereas HA‐CPPI was most often associated with Staphylococcus aureus (11.6%) and Gram‐negative (31.9%) infections. Mortality was high during hospitalization (CA‐CPPI 13.4% vs HA‐CPPI 16.6%; P = 0.417) and at 1 year (CA‐CPPI 32.4% vs HA‐CPPI 45.5%; P = 0.006). Conclusion: This is the first large multicentre epidemiological study of pleural infection in Australian adults and includes the largest cohort of HA‐CPPI published to date. CPPI is caused by a diverse range of organisms which vary between CA and HA sources. CPPI is a poor prognostic indicator both in the short term and in the subsequent 12 months. Abstract : Pleural infection is common, with notable geographical variations in bacteriology. This state‐wide longitudinal study provides the largest data set of bacteriology and outcomes of Australian adults with culture‐proven pleural infection. Pleural infection is a major burden with significant length of hospital stay, high inpatient and 12‐month mortality and diverse bacteriology between community‐ and hospital‐acquired cases. See related Editorial